Insights from the Silent: Exploring Deaf Individuals' Perspectives on Using Learning Management Systems for Online Learning - Jati Suryanto; Puteri Nabilah Ramadhani; Juang Kurniawan Syahruzah; Maryam Sorohiti (Tell : Teaching of English Language and Literature Journal, 2024)
The COVID-19 pandemic has led to a surge in the popularity of online learning, offering students greater flexibility and accessibility. However, students with hearing impairments encounter significant challenges in accessing learning materials and communicating with teachers and peers. This study aims to investigate the experiences of students with hearing impairments using a Learning Management System (LMS) for online learning focusing on their challenges they face and the strategies they employ in their learning. The research was conducted using a descriptive qualitative design at private universities in Yogyakarta. Semi-structured interviews were conducted to gather the data involving three students with hearing impairments who have used LMS in online learning as the participants. The findings revealed the challenges that included the use of multiple applications, lack of understanding on the LMS, lack of LMS notifications, material mismatch, unstable internet connection, tool constraints, lack of inadequate facilities, and there is no training on the use of the LMS. Additionally, the strategies used by the students included self-study, assignment submission via email, asking others for help, using additional apps, using a typist facility, and joining WhatsApp group discussions.